Emotion-based learning: insights from the Iowa Gambling Task - Turnbull, Oliver H.; Bowman, Caroline; Shanker, Shanti; Davies, Julie (Frontiers in Psychology, 2014)
Interest in the cognitive and/or emotional basis of complex decision-making, and the related phenomenon of emotion-based learning, has been heavily influenced by the Iowa Gambling Task. A number of psychological variables have been investigated as potentially important in understanding emotion-based learning. This paper reviews the extent to which humans are explicitly aware of how we make such decisions; the biasing influence of pre-existing emotional labels; and the extent to which emotion-based systems are anatomically and functionally independent of episodic memory. Systematic review suggests that (i) an aspect of conscious awareness does appear to be readily achieved during the IGT, but as a relatively unfocused emotion-based ‘gut-feeling’, akin to intuition; (ii) Several studies have manipulated the affective pre-loading of IGT tasks, and make it clear that such labelling has a substantial influence on performance, an experimental manipulation similar to the phenomenon of prejudice. (iii) Finally, it appears that complex emotion-based learning can remain intact despite profound amnesia, at least in some neurological patients, a finding with a range of potentially important clinical implications: in the management of dementia; in explaining infantile amnesia; and in understanding of the possible mechanisms of psychotherapy.